Mode choice modelling method to shift car travelers towards park and ride service - Memon, I.A. (Asian Research Publishing Network, 2016)
Urban transportation planning has a key role in the daily routine of inhabitants. Transportation planning has been observed as the most debatable subject, but least attention has been paid on it. Traffic congestion is expanding up to the outskirts of city centers during peak hours. It is perceived as an unresolved urban transportation problem for the inhabitants of urban areas such as Karachi. To resolve this issue, park-and-ride service (P and RS) is considered as a sustainable approach and major contributory in urban areas to reduce the traffic congestion from city centers. P and RS has been successfully implemented and became beneficiary in many countries of the world. Particularly it helps to reduce traffic congestion at a city center, and as a result it reduces the reliability of private vehicles. The objective of this research is to develop a model to shift car travelers' towards P and RS and study the factors which influence car travelers' choice of mode. This study can help stakeholders with useful information for future planning and development of P and RS in Karachi, Putrajaya and Surabaya. The findings revealed the reasons, why car travelers are discouraged to use P and RS facility. Discrete choice modelling is discussed to analyze the factors that encourage users to switch their mode choice towards P and RS. Research outcomes will support policy making and provides base for the future study on the mode choice model for P and RS. Â© 2006-2016 Asian Research Publishing Network (ARPN).